EFEKTIVITAS PROGRAM PENJANGKAUAN DI KALANGAN PENGGUNA NARKOBA SUNTIK DALAM MENURUNKAN PERILAKU BERISIKO HIV - Suparno Heru; Ferdinand Siagian; Amry lsmail; Sari Aznur; James Blogg (Jurnal Kependudukan Indonesia, 2010)
The effort to control the spread of HIV in the IDUs (Injection Drug Users) group started in 1999 in Bali and in Jakarta in 2001. The strategy is to adopt the concept of Harm Reduction (HR) with its main activities is outreach. The general objective of the study is to assess the effectiveness of outreach program to reduce risk behaviors related with HIV/AIDS among IDUs. This study is conducted quantitative and qualitative survey. The design of quantitative survey is using Cross Sectional Post only with Comparison Group Evaluation Design, while focus group discussions, in-depth interviews and observations are using in qualitative survey. In general, the process of outreach program has well done by program implementer, but this activity has not been reduced HIV risk behaviors consistently. The high intensity of injection, the strong bonds of friendship, social norms that do not support and stigmatization toward IDUs are the constraints that dominate the behavior change effort. Meanwhile, the limited of outreach workers is also the obstacle to run this program properly.